The influence of the environment on the spin evolution of low-mass stars - I. External photoevaporation of circumstellar discs - Roquette, Julia; Matt, S P; Winter, Andrew J.; Amard, L; Stasevic, S (Monthly notices of the Royal Astronomical Society, 2021)
Massive stars are strong sources of far-ultraviolet radiation that can be hostile to the evolution of protoplanetary discs, driving mass-loss by external photoevaporation and shortening disc-dissipation time-scales. Their effect may also reduce the time-scale of angular momentum exchanges between the disc and host star during the early pre-main-sequence phase. To improve our understanding of the environmental influence on the rotational history of stars, we developed a model that considers the influence of the local far-ultraviolet radiation on the spin evolution of low mass stars. Our model includes an assumption of disc locking, which fixes the rotation rate during the star-disc-interaction phase, with the duration of this phase parametrized as a function of the local far-ultraviolet radiation and stellar mass (in the range of 0.1-1.3 M⊙). In this way, we demonstrate how the feedback from massive stars can significantly influence the spin evolution of stars and explain the mass dependence observed in period-mass distributions of young regions like Upper Sco and NGC 2264. The high far-ultraviolet environments of high-mass stars can skew the period distribution of surrounding stars towards fast-rotation, explaining the excess of fast-rotating stars in the open cluster h Per. The proposed link between rotation and the pre-main-sequence environment opens new avenues for interpreting the rotational distributions of young stars. For example, we suggest that stellar rotation may be used as a tracer for the primordial ultraviolet irradiation for stars up to ∼1 Gyr, which offers a potential method to connect mature planetary systems to their birth environment.
Gesehen am 17.12.2021